(untitled) (Research, Society and Development, 2023)
Introduction: The literature points out that creatine supplementation may be linked to a decrease in cognitive deficit. Objective: The present study aims to discuss the relationship between creatine supplementation and memory. Methodology: The search for articles was carried out in the database: Pubmed, published between the years 2019 and 2023, using the descriptors "memory", "creatine", "supplementation", "dementia", "alzheimer". 108 articles were found and 6 were used. Results: Trials in mice and the elderly have shown a potential to improve cognitive processing, especially in the elderly with conditions characterized by chronic pathologies such as deficiencies in creatine synthesis enzymes, mild traumatic brain injury and Alzheimer’s disease. Conclusion: Although there is evidence that there is a correlation between creatine supplementation and the improvement of cognitive deficit, more studies are needed to trace the complete mechanism between these two conditions.